Geographic isolation and vulnerability across Peru’s ecological regions: the influence of regional contexts of extraction - Bazo Zambrano, Juan Carlos (2023)
Geographically isolated places are often sites of exported environmental risks, intense resource extraction,exploitation and marginalization, and social policy neglect. These conditions create unique challengesrelated to vulnerability and adaptation that have direct disaster management implications. Our researchinvestigates the relationship between geographic isolation and flood-related social vulnerability across Peru’secological regions. Ecoregions have different relationships with colonialism and capitalism that shapevulnerability, and we hypothesize that the relationship between vulnerability and geographic isolation variesacross ecoregions. Using mapping techniques and spatial regression analysis, we find that relationshipsbetween vulnerability and geographic isolation vary regionally, with differences that suggest alignment withregional contexts of extraction. We find notable differences in vulnerability related to public healthinfrastructure and access to services and between ecoregions with sharply contrasting histories of naturalresource extraction and investment and disinvestment.